Breaking through undergraduate thesis writing barriers: insights from Indonesian EFL students - Alkhasanah, Ainun Nisa; Kholis, Nur (Erudita: Journal of English Language Teaching, 2024)
Many EFL students experience barriers to completing their final project writing of the thesis, which is required for graduation. In response to this, this study aims to explore students’ barriers and potential solutions in writing their undergraduate theses. The research was designed with qualitative method employing a case study approach. Five undergraduate students in an Islamic university in Pekalongan, Central Java, Indonesia were recruited to participate in this study, regarding the criteria: the EFL students completed writing their theses and signed a consent form. Data were garnered through interviews and document analysis. The data were analyzed using thematic analysis. The study findings demonstrate that the undergraduate EFL students faced several barriers to their thesis writing. The barriers dealt with psychological, sociocultural, and linguistic problems. The most common and frequently mentioned problems from interviews were barriers with psychological factors, sociocultural factors, and linguistic factors. This study also portrays that the participants found various solutions to tackle the barriers when writing their theses, including cognitive solutions, metacognitive solutions, affective solutions, and social solutions. The present study concludes with practical implications for how university EFL students overcome the problems faced in writing an undergraduate thesis.